Korelasi Efikasi Diri Bidan dan Kesiapan dalam Melakukan Komplementer Baby Spa Sebagai Upaya Pencegahan Komplikasi di Kawasan Pesisir - Tanti Tri Lestary; Elisa Danik Kurniawati; Nur Citra; Nurahmi Umami; Safinatun Najah; Vinny Alvionita (Jurnal Kesehatan Indonesia, 2024)
Child development is an important indicator in assessing the health status of a community. The critical of growth and development period starts from the womb until the age of 2 years, so it is often called the “Golden Period”. Efforts to improve child growth and development is done comprehensively by providing quality stimulation can prevent complications and support optimal growth and development. Baby Spa is beneficial for developing the nervous system, reduce stress, improve sleep quality, physical physical motor skills, balance, coordination coordination of body movements, thus becoming a recommended complementary therapy for optimize infant growth and development. Research Objective: Knowing the correlation of midwives' self-confidence withreadiness in performing Baby Spa as an effort to prevent complications in coastal areas. Methods: used a cross-sectional approach approach with a population of 38 midwives and selected based on total sampling and have attended Baby Spa training. The research tool was an e-Questionnaire using the General Self- Confidence Scale (GSES). Furthermore, the data were analyzed Chi Square test to see the correlation between variables. Results: p value 0.037 <0.05 so that it is stated that there is a significant correlation between midwives' self-confidence and readiness to do Baby Spa to prevent complications in coastal areas. Conclusion of this study It can be concluded that there is a significant correlation between.